1975
DOI: 10.1073/pnas.72.10.3978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA of isolated chromatin subunits.

Abstract: Partial digestion of rat liver nuclei with staphylococcal nuclease results in the liberation of nucleoprotein complexes consisting of one or more v bodies. By velocity centrifugation we have isolated the monomeric subunit in relatively pure form. We find that this subunit contains 185 base pairs of DNA and 240,000 daltons of protein, resulting in a protein to DNA ratio identical to that of unperturbed chromatin. The isolated monomeric particle is further susceptible to internal nuclease attack resulting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…Extended nonbeaded states of chromatin with the full nucleosomal histone complement have so far been described only in high urea concentrations (for references, see Olins et al ., 1977). The findings in various laboratories that transcriptional complexes and/or sequences complementary to transcriptional products can be recovered in the nucleosomal fraction obtained by nuclease digestions (for example, Lacy and Axel , 1975;Gottesfeld et al ., 1975;Garel and Axel, 1976;Mathis and Gorovsky , 1976;Kuo et aI. , 1976;Piper et aI., 1976;Reeves and Jones, 1976;Reeves, 1976Reeves, , 1977Brown et al ., 1977) are not contrad ictory to the conclusion that nucleosomal beads are absent in chromatin regions engaged in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Extended nonbeaded states of chromatin with the full nucleosomal histone complement have so far been described only in high urea concentrations (for references, see Olins et al ., 1977). The findings in various laboratories that transcriptional complexes and/or sequences complementary to transcriptional products can be recovered in the nucleosomal fraction obtained by nuclease digestions (for example, Lacy and Axel , 1975;Gottesfeld et al ., 1975;Garel and Axel, 1976;Mathis and Gorovsky , 1976;Kuo et aI. , 1976;Piper et aI., 1976;Reeves and Jones, 1976;Reeves, 1976Reeves, , 1977Brown et al ., 1977) are not contrad ictory to the conclusion that nucleosomal beads are absent in chromatin regions engaged in transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Biophysical and electron microscopic methods have indicated that high salt causes chromatin to become less compact (25,28). Assuming that the viral transcription complex contains nucleosomes, as appears to be the case for template active cellular chromatin (18)(19)(20), a salt-mediated conformational change such as the conversion from an octamer to two tetramers may facilitate a maximal rate of RNA chain elongation in nucleosomal DNA, at least in vitro.…”
Section: H-rna ( ); 14c-vtc (---); 14c-dna (---)mentioning
confidence: 99%
“…Nucleosomes are comprised of about 200 base pairs of DNA wound around a complex containing two each of the four major histones (11)(12)(13)(14)(15)(16)(17). Transcriptionally active and inactive regions of cellular chromatin are both organized in this basic manner (18)(19)(20), although there is some structural difference between them, as evidenced by a selective deoxyribonuclease I sensitivity of active genes (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive eucaryotic feature is that the genomic DNA is organized into nucleosomes by intimate association with histones and other proteins to form chromatin. Treatment of chromatin with micrococcal nuclease results in a characteristic nucleosome repeat structure (16). Moreover, chromatin can exist in both transcriptionally active and inactive forms.…”
mentioning
confidence: 99%